THE EFFECTIVENESS OF LOCAL WISDOM-BASED COUNSELING TO PREVENT IRON DEFICIENCY ANEMIA AMONG PREGNANT WOMEN: A PROTOCOL OF A RANDOMIZED CONTROLLED TRIAL - Darmawati Darmawati; Tongku Nizwan Siregar; Hajjul Kamil; Teuku Tahlil (Belitung Raya Foundation, Indonesia, 2020)
Background: Anemia during pregnancy is a health problem that often occurs in developing countries. Local wisdom-based counseling is considered a new approach in preventing iron deficiency anemia among pregnant women by integrating cultural beliefs into antenatal counseling. Objective: The study aims to measure the effectiveness of local wisdom-based counseling model among pregnant women to prevent iron deficiency anemia. Methods: This paper outlines the protocol of a randomized controlled trial method. Two intervention programs will be developed, the local wisdom-based program and health-based counseling intervention program, and will be tested among 150 pregnant women from nine public health centers in one district of Aceh Province. Sample selection will be completed through a simple random selection process. The effectiveness of the interventions will be assessed using a self-report questionnaire and a hemoglobin test. Data will be analyzed using descriptive and inferential statistics. Discussion: The expected outcome in this study is a significant difference in hemoglobin levels between both intervention groups. It is also expected that there will be an increase in knowledge, attitude, and behavior in the group who will receive local wisdom-based counseling intervention than the other group who will receive health-based counseling intervention. A local wisdom-based counseling approach is expected to give an effective model to reduce the prevalence of iron deficiency anemia among pregnant women. The effectiveness of this model may suggest the further application in the other regions. Registration trial number: ACTRN12620000299909